Aktivitas Madu sebagai Antibakteri Staphylococcus aureusdan Escherichia ColiO157:H7 - Suwito, Widodo; Andriani, Andriani; Amelia, Iis; Rohmayanti, Titi; Haris, Helmi; Karimy, Moh Faiz (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Honey is a natural substance from flower nectar and produced by honey bees. The honey has been used as healing. The study was conducted to determine the antibacterial activity of Blora and Kaliandra honey against pathogenic bacteria such as Staphylococcus aureus (S. aureus) and Escherichia coli O157:H7 (E. coli O157:H7). As a comparison, was used commercial honey. The results showed Blora and Kaliandra honey had antibacterial activity, however the commercial honey has not antibacterial activity. Kaliandra honey has antibacterial activity against S. aureus and E. coli O157:H7 better than Blora and commercial honey. Concentration 25% of Kaliandra honey was able to inhibit S. aureus, while blora honey showed antibacterial activity at 50% and commercial honey did not show antibacterial activity until concentration 50%. Inhibition zone of S. aureus produced by Kaliandra honey with concentration 25 and 50% were 8.0 ± 0.1 mm and 9.0 ± 0.2 mm respectively and concentration 50% Blora honey was 7.3 ± 0.1 mm. Inhibition zone of E. coli O157:H7 produced by concentration 50% Kaliandra honey was 8.0 ± 0.3 mm and Blora honey was 7.7 ± 0.1 mm. The study showed that Blora and Kaliandra honey have antibacterial activity and can be used as alternative substitution in antibiotic therapy.